Risk factors for Hyponatremia in COVID-19 hospitalised patients - Anees, Muhammad; Raza, Muhammad; Farooq, Omair`; Mumtaz, Asim (Pakistan Journal of Medical Sciences, 2022)
Objectives: To determine the risk factors for Hyponatremia in Coronavirus disease 2019 (COVID-19) patients.Methods: Medical records of all patients admitted in COVID-19 Isolation Intensive Care Unit of Farooq Hospital Westwood Branch, Lahore from 1st July to 30th September, 2020 were retrospectively reviewed. Patients with confirmed diagnosis of COVID-19 by Real Time Polymerase Chain Reaction (RT-PCR) and having Hyponatremia (serum Sodium (s/Na+ <135mEq/L) were included, patients with Eunatremia (s/Na+ within 135 - 145mEq/L) were taken as control while subjects with Hypernatremia (s/Na+ >145mEq/L) at admission, incomplete medical records and pregnant females were excluded from the study. Demographic, clinical and laboratory data at time of admission in hospital was extracted.Results: Of 182 included patients, 79.1% (n=144) were male 40.7% (n=74) had Diabetes Mellitus (DM) and 44.5% (n=81) were hypertensive. Forty seven percent (n=86) patients had Hyponatremia while 52.7% (n=96) were eunatremic. Forty nine percent (n=90) patients had Acute Kidney Injury (AKI) and 4.9% (n=9) patients died. Risk factors for Hyponatremia were age >60 years (OR=2.52, p=0.006); DM (OR=2.79, p=0.001); Hypoxemia (OR=3.74, p<0.001); Lymphopenia (OR=7.62, p<0.009); Hypoalbuminemia (OR=9.15, p<0.001); high serum Ferritin (OR=4.46, p<0.001), high Neutrophil to Lymphocyte Ratio (NLR) (OR=3.58, p<0.001) and AKI (OR=3.40, p<0.001).Conclusions: Hyponatremia was common in COVID-19 hospitalized patients. Increasing age, DM, Hypoxemia, Hypoalbuminemia, high serum Ferritin and AKI were the most significant risk factors for Hyponatremia. Hyponatremic patients had comparatively higher mortality than Eunatremic patients.doi: https://doi.org/10.12669/pjms.39.1.5466How to cite this: Anees M, Raza M, Farooq O, Mumtaz A. Risk factors for Hyponatremia in COVID-19 hospitalised patients. Pak J Med Sci. 2023;39(1):274-279. doi: https://doi.org/10.12669/pjms.39.1.5466This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.